Not Only Sex: Introduction to the Pornography of Death - Pacek, Agnieszka (Media - Culture - Social Communication, 2019)
The aim of this article is a presentation of the pornography of death. This phenomenon was described for the first time by English anthropologist Geoffrey Gorer. Generally, this issue is linked with the presentation of violent death images in different media, excluding images of so-called “natural death”, regarding the tabooisation of death in modern Western societies. Furthermore, the work entitled: Cannibalism of the eye by French anthropologist Louis-Vincent Thomas has been outlined. The author also discussed the consequences of issues regarding the perception of such images.